Arthroscopic all-inside wrapping repair of lateral meniscus bucket-handle tears: clinical and imaging outcomes - Kun-Hui Chen; Hsuan-Hsiao Ma; Alisan Fu; Hsin-Yi Wang; Hsiao-Li Ma; En-Rung Chiang (Journal of Orthopaedic Surgery and Research)
Abstract Purpose This study aimed to assess the clinical and radiographic healing rates of the arthroscopic all-inside wrapping repair technique for lateral meniscus bucket-handle tears (LMBHTs). Methods This retrospective study examined patients diagnosed with LMBHTs who underwent all-inside wrapping repair with or without anterior cruciate reconstruction between 2012 and 2021. Patients with previous knee surgeries, multiligamentous knee injuries, or advanced osteoarthritis were excluded. Clinical follow-up was at least 2 years. Clinical healing was defined as no reoperation of LMBHTs following initial repair and the absence of symptoms related to the LMBHT during follow-up. Postoperative clinical outcomes were assessed using the International Knee Documentation Committee (IKDC) score. At 6 months postoperatively, the healing of the repaired meniscus was evaluated using Henning’s criteria through magnetic resonance imaging (MRI). Results Of the 34 patients included, two required re-operation for a re-tear of the BHT, resulting in a clinical healing rate of 94.1% (95% confidence interval [CI]: 82.9–99.2%) at a mean follow-up of 4.2 years. Among the remaining 32 patients, the mean postoperative IKDC score was 83.7 ± 8.2 (range, 70–95). MRI evaluations at 6 months postoperatively revealed complete healing in 64.7% (22/34; 95% CI: 47.9–79.5%), partial healing in 23.5% (8/34), and failure to heal in 12.5% (4/34, including the two re-tear cases). Subgroup analyses indicated no significant difference in the IKDC scores between patients with complete healing and those with partial healing on MRI (85.5 ± 7.9 vs. 82.3 ± 8.5; p = 0.53). Future studies with larger cohorts and stratified analyses are needed to explore potential predictors of healing outcomes. Conclusions The all-inside wrapping repair technique demonstrated favorable outcomes in patients with lateral BHTs and can be used as a viable alternative.